2016
DOI: 10.1016/j.foodhyd.2016.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Adding neutral or anionic hydrocolloids to dairy proteins under in vitro gastric digestion conditions

Abstract: Elsevier Borreani, JAA.; Llorca Martínez, ME.; Larrea Santos, V.; Hernando Hernando, MI. (2016). Adding neutral or anionic hydrocolloids to dairy proteins underin vitro gastric digestion conditions. Food Hydrocolloids. 57:169-177. doi:10.1016/j.foodhyd.2016.01.030. IntroductionOver recent decades, the problems of overweight and obesity have increased and, therefore, the interest in formulating satiating foods has grown. The concept of appetite control comprises two components: satiation (the processes that ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 38 publications
3
36
0
1
Order By: Relevance
“…This obviously indicated that complete hydrolysis of bovine milk proteins by the immobilized trypsin was carried out within 30 min (Bkhairia et al, 2016). As can be seen in the electrophoregram, bovine milk proteins were cleaved by immobilized trypsin more effectively with increasing time up to 30 min (Borreani, Llorca, Larrea, & Hernando, 2016). It can be concluded that hydrolysis of bovine milk by immobilized trypsin was very effective.…”
Section: Sds-page Patterns Of Bovine Milk Hydrolyzed By Immobilized Tmentioning
confidence: 75%
“…This obviously indicated that complete hydrolysis of bovine milk proteins by the immobilized trypsin was carried out within 30 min (Bkhairia et al, 2016). As can be seen in the electrophoregram, bovine milk proteins were cleaved by immobilized trypsin more effectively with increasing time up to 30 min (Borreani, Llorca, Larrea, & Hernando, 2016). It can be concluded that hydrolysis of bovine milk by immobilized trypsin was very effective.…”
Section: Sds-page Patterns Of Bovine Milk Hydrolyzed By Immobilized Tmentioning
confidence: 75%
“…Rosell & Foegeding (2007) studied lower protein solubility in HPMC-gluten systems and suggested that HPMC could have an interfering role in protein network formation. Borreani et al (2016) reported that the aggregates formed in the dairy protein-konjac glucomannan mixtures. These results were also demonstrated by Ribotta et al (2005), who found the carrageenan and pectin decreased the density of wheat protein bands because of forming hydrophilic complexes with gluten proteins.…”
Section: Fig 2 Exhibits the Typical Protein Electrophoretic Profilesmentioning
confidence: 99%
“…() found that the whey proteins/alginate complex became larger with the addition of alginate and remained largely unchanged after gastric digestion, which was due to the strong interaction between the opposite charges of whey proteins and alginate. It was indicated that a combination of whey proteins and alginate could be used to delay gastric emptying and promote satiety (Borreani et al ., ). In this study, the combination of digested TPS samples and α‐amylase might be the mechanism of α‐amylase inhibitory effects.…”
Section: Resultsmentioning
confidence: 99%